Noise-Induced Transitions for an SIV Epidemic Model with Medical-Resource Constraints (Journal of Nonlinear Modeling and Analysis, 2024)
We consider a stochastically forced epidemic model with medical-resource constraints. In the deterministic case, the model can exhibit twotype bistability phenomena, i.e., bistability between an endemic equilibriumor an interior limit cycle and the disease-free equilibrium, which means thatwhether the disease can persist in the population is sensitive to the initialvalues of the model. In the stochastic case, the phenomena of noise-inducedstate transitions between two stochastic attractors occur. Namely, under therandom disturbances, the stochastic trajectory near the endemic equilibriumor the interior limit cycle will approach to the disease-free equilibrium. Besides,based on the stochastic sensitivity function method, we analyze the dispersionof random states in stochastic attractors and construct the confidence domains(confidence ellipse or confidence band) to estimate the threshold value of theintensity for noise caused transition from the endemic to disease eradication.